Gender Mainstreaming - an Innovation in Europe? : the Institutionalisation of Gender Mainstreaming in the European Commission. - Schmidt, Verena (Verlag Barbara Budrich, 2005)
The concept of gender mainstreaming has experienced an unexpected boom in the European Union and beyond since the United Nations World Conference of Women in Beijing in 1995. Starting from the evolution of gender mainstreaming, this book examines the extent to which gender mainstreaming can be regarded as an innovation and as an institution in a complex organisation like the European Commission. By ensuring that the effects on both genders of all policies and organisational processes are taken into account, gender mainstreaming seeks to bring what are often marginalised as ´women´s concerns´ into the mainstream of the analysis. Gender mainstreaming is often regarded as a paradigm shift compared to previous concepts of equal treatment and positive action programmes.